Pengaruh Brand Image dan Kualitas Produk terhadap Keputusan Berkunjung ke Resto Foresthree - Annisa Rizkia Arif; I Made Adhi Gunadi (Journal of Tourism Destination and Attraction, 2018)
This research at Foresthree restaurant is aimed to determine the influence of brand image and product quality on visiting decisions. There are several factors influencing a visiting decision, therefore this research aim to know the influence of brand image and product quality. The research method used is a quantitative method, where the variables to be tested are corporate image, product image, user image variables according to Aaker and Biel (1993) theory and product quality according to West, Wood, and Harger (2006). Data is collected by interviews and questionnaires conducted in July 2018 with purposive sampling technique. Data is presented in quantitative descriptive manner. The findings of this research indicate that the corporate image and product image variables have a significant effect on the decision to visit Foresthree restaurant, while the user image and product quality have no significant effect on the decision to visit Foresthree restaurant.